Does Stricter Command-and-Control Environmental Regulation Promote Total Factor Productivity? Evidence from China’s Industrial Enterprises - Wei Chen; Luwen Gao; Xing Xu; Yan Zeng (Discrete Dynamics in Nature and Society)
China is implementing increasing stringent command-and-control environmental regulations to achieve high-quality development. However, we have limited understanding about whether such policies are effective. This study selects the policy of China’s National Environmental Protection “Eleventh Five-Year Plan” as a quasi-natural experiment and uses the difference-in-differences (DID) method to analyze the effect of stricter command-controlled environmental regulations on total factor productivity from the enterprise level. Our results indicate that stricter command-and-control environmental regulation promotes TFP of enterprises throughout the country. This effect is even greater in long-established, large-scale, or low capital density enterprises. In addition, stricter command-and-control environmental regulation has a greater positive effect on the TFP of companies in industries with high pollution intensity and fierce competition. Furthermore, government transformation and market green preference will magnify the positive effect of stricter command-and-control environmental regulation on corporate TFP. Moreover, stricter command-and-control environmental regulation promotes the growth of enterprise TFP mainly by improving the efficiency of resource allocation within and between enterprises, rather than stimulating innovation. Local governments should refine pollution control policies, optimize the external environment, and enhance the innovation power of enterprises.